PERANCANGAN SISTEM INFORMASI EKSPEDISI RAWAT JALAN DI RUMAH SAKIT SARININGSIH - Nida Khoerun Nisa; Nadhifa Trirani Azzahra; Meira Hidayati; Falaah Abdussalaam (Al Tamimi Kesmas: Jurnal Ilmu Kesehatan Masyarakat (Journal of Public Health Sciences), 2021)
TheBook Expedition is a book that contains patient data, used for proof of handoverfiles medical record offrom the medical record unit to the polyclinic, to support the needs of outpatient services. At Sariningsih Hospital the recording of expedition books still uses manual recording assisted by Microsoft Excel, thus making delays provision of medical record files and delays in returning medical record files. For this reason, an Outpatient Expedition system is made, so that the process of returning medical record files is more regular and outpatient services at the hospital are more effective. For this reason, themethod waterfall and UML (Unfield Modeling Language) are used.The result of this research is an outpatient expedition system. Of course it can provide convenience to medical record officers. Keywords: Information System, Medical Record Expedition, Xampp, Sublime, Diagram UML.